Analisa Tebal dan Perpanjangan Landasan Pacu pada Bandar Udara Internasional Sultan Mahmud Badaruddin II - Hastha Yuda Pratama (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2015)
In South Sumatra, especially in Palembang, total passengers of air transport increased annually. The infrastructure of airfield must be improved, the needed of extension of landing and take-off area aircraft. This research includes the